2010
DOI: 10.3892/or_00000815
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 inhibitors induce desensitization of EGF receptor via p38 MAPK-mediated phosphorylation at Ser1046/1047 in human pancreatic cancer cells

Abstract: Abstract. Heat shock protein (HSP) 90 is known to be a molecular chaperone whose association is required for the stability and function of oncogenic protein including epidermal growth factor receptor (EGFR) that promotes cancer cell growth. Therefore, HSP90 is a promising target for therapy against cancer including in the pancreas, some of which are highly dependent on EGFR. We investigated the effects of HSP90 inhibitors on cytotoxicity and desensitization of EGFR in human pancreatic cancer cells (KP3, BxPc3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…We have previously reported that HSP90 inhibitors as well as (-)-epigallocatechin gallate downregulates EGFR via phosphorylation at S1046/7 by p38 MAPK in human colon and pancreatic cancer cells (33,35). In addition, there is accumulating evidence that activation of p38…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that HSP90 inhibitors as well as (-)-epigallocatechin gallate downregulates EGFR via phosphorylation at S1046/7 by p38 MAPK in human colon and pancreatic cancer cells (33,35). In addition, there is accumulating evidence that activation of p38…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibition of HSP90 functions has become as one of the leading strategies for anticancer chemotherapeutics [4,5]. In our previous study [6], we have demonstrated that HSP90 inhibitors such as geldanamycin [7], 17-allylamino-17demethoxy-geldanamycin (17-AAG) [8] and 17-dimethylamino-ethylamino-17-demethoxy-geldanamycin (17-DMAG) [9], cause epidermal growth factor receptor (EGFR) desensitization in human pancreatic cancer cells, and that the activation of p38 mitogen-activated protein (MAP) kinase induced by HSP90 inhibitors regulates the desensitization of EGFR via its phosphorylation at Ser1046/7. HSP90 inhibitors, by interfering the N-terminal domain ATP binding site of HSP90, cause the destabilization and eventual degradation of HSP90 client proteins, and then lead to inhibit ATP-dependent HSP90 chaperone activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that downregulation of EGFR induced by namitecan as well as by cetuximab treatment correlated with the internalization and increased ubiquitination of EGFR, which occurred independently of c-Cbl, an ubiquitin ligase responsible for EGFR degradation after EGF binding (5,31,33). It has previously been reported that other drugs induce downregulation of EGFR without the requirement of c-Cbl binding (34,35,(41)(42)(43)(44). In particular, epigallocatechin gallate and 17-N-allylamino-17-demethoxygeldanamycin cause EGFR downregulation via phosphorylation at Ser1046/1047 by p38 MAPK in different tumor cell lines (42).…”
Section: Discussionmentioning
confidence: 49%
“…It has previously been reported that other drugs induce downregulation of EGFR without the requirement of c-Cbl binding (34,35,(41)(42)(43)(44). In particular, epigallocatechin gallate and 17-N-allylamino-17-demethoxygeldanamycin cause EGFR downregulation via phosphorylation at Ser1046/1047 by p38 MAPK in different tumor cell lines (42). Although phosphorylation of serine residues and of Tyr1045 is essential for EGFinduced receptor ubiquitination (32, 41), Oksvold and colleagues (45) found that only the serine residues are critical for EGFR internalization and degradation.…”
Section: Discussionmentioning
confidence: 99%